MENTAL LEXICON ON THE JAVANESE WORDS AMONG FOURTH YEAR STUDENTS OF ENGLISH STUDY PROGRAM AT UNIVERSITAS BRAWIJAYA - RIHI, ESTER OKTAVIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
At least 45% of the Indonesian population are the people who live in an area where Javanese is the dominant language. In having conversation, it is essential for Javanese to be polite, not only our utterances but also our body language. In East Java, there are 5 language variations among the society due to the strategic boundaries; nearby Central Java, Madura Island, and Bali Island. This research is conducted to 3 language variations in East Java, namely: Surabaya Dialect, Mataraman Dialect, and Padhalungan Dialect. In order to see the mental storage of Javanese, the writer uses Word Association Test (WAT) through Javanese words. There are two problems to be solved, namely: (1) what are the participants’ responses of the stimulus words; (2) what kind of types shown in WAT in the participants’ responses.            The participants who join the test were 35 students consisting of: 15 students come from Surabaya dialect, 14 students come from Mataraman dialect, and 9 students from Padhalungan dialect. All of them are the 4th year students of English Study Program at Universitas Brawijaya. This study proposes qualitative approach since it could show the reality in the social life clearly in different dialects around East Java. The participants were gathered into a class, then given a questionaire consisting 8 stimulus words.            The result of this study reveals that the East Javanese students having different dialect store the Javanese words differently, although the findings did not lead to the big gap among the three groups. The Surabaya and Padhalungan dialects had more syntactical relation in the responses; while Mataraman was paradigmatic relation. In terms of Javanese styles, the findings revealed that the Surabaya and Padhalungan dialect had a similiar pattern in terms of the use of Ngoko Javanese. While the participants from Mataraman dialect tended to use a more polite form.                   In the future, the writer hopes there will be more students in the Faculty of Cultural Studies who conduct Mental Lexicon as the focus of study; since there were still limited number of students who want to deal with this subject. Also, this research of Psycholinguistics can be a guidance for the students for a reference. For further researcher, a suggestion to make research in another topic such as: the comparison between language variation differences to be the next case study.Keywords: mental lexicon, word association test, Javanese words.